Peran Kotbah Gembala Sidang Dalam Pertumbuhan Rohani Jemaat Menurut John Chrysostom - Hisikia gulo; Hendi Hendi (CARAKA: Jurnal Teologi Biblika dan Praktika, 2021)
AbstractThe preaching role of the pastor of the congregation in the spiritual growth of the congregation has a major contribution to the salvation of every soul. This article discusses and describes the role of the pastor as a preacher in the spiritual growth of the church taught by John Chrysostom. Every pastor as a preacher must reach 3 depths of approach to preaching the word of God; Cognitive, Affective and Psychomotor. It is through the preaching of the word of God which is taught by a pastor so that someone understands and understands the meaning of following and imitating the great shepherd, Jesus Christ, and carrying out each of His teachings. The spiritual growth of each congregation is influenced by each pastor's role as the preaching of the word of God through 3 depth approaches with the aim of the need for the purity of one's soul leading to spiritual maturity. AbstrakPeran khotbah gembala sidang dalam pertumbuhan rohani jemaat memiliki kontribusi besar bagi keselamatan setiap jiwa. Artikel ini membahas dan menguraikan peran gembala sidang sebagai pengkhotbah dalam pertumbuhan rohani jemaat yang di ajarkan oleh John Chrysostom. Setiap gembala sidang sebagai pengkhotbah harus mencapai 3 kedalaman pendekatan pemberitaan firman Allah; Kognitif, Afektif dan Psikomotorik. Melalui pemberitaan firman Allah yang di ajarkan oleh seorang gembala sidang sehingga seseorang mengerti dan memahami arti dari mengikut dan meneladani gembala agung yaitu Yesus Kristus serta melakukan setiap ajaran-Nya. Pertumbuhan rohani setiap jemaat di pengaruhi dari setiap peran gembala sidang sebagai pemberitaan firman Allah melalui 3 kedalaman pendekatan dengan tujuan kebutuhan akan kemurnian jiwa seseorang menuju kepada kedewasaan rohani. Kata-kata Kunci: Gembala Sidang; Kedewasaan; Peran; Pengkhotbah.